Particle physics experiments based on the AWAKE acceleration scheme. (24th June 2019) - Wing, M.
Abstract : New particle acceleration schemes open up exciting opportunities, potentially providing more compact or higher-energy accelerators. The AWAKE experiment at CERN is currently taking data to establish the method of proton-driven plasma wakefield acceleration. A second phase aims to demonstrate that bunches of about 10 9 electrons can be accelerated to high energy, preserving emittance and that the process is scalable with length. With this, an electron beam ofO (50 GeV) could be available for new fixed-target or beam-dump experiments searching for the hidden sector, like dark photons. The rate of electrons on target could be increased by a factor of more than 1000 compared to that currently available, leading to a corresponding increase in sensitivity to new physics. Such a beam could also be brought into collision with a high-power laser and thereby probe the completely unmeasured region of strong fields at values of the Schwinger critical field. An ultimate goal is to produce an electron beam ofO (3 TeV) and collide with an Large Hadron Collider proton beam. This very high-energy electron–proton collider would probe a new regime in which the structure of matter is completely unknown. This article is part of the Theo Murphy meeting issue 'Directions in particle beam-driven plasma wakefield acceleration'.